2015
DOI: 10.1586/14789450.2015.1104251
|View full text |Cite
|
Sign up to set email alerts
|

Hyperamylinemia as a risk factor for accelerated cognitive decline in diabetes

Abstract: Type II diabetes increases the risk for cognitive decline via multiple traits. Amylin is a pancreatic hormone that has amyloidogenic and cytotoxic properties similar to the amyloid-β peptide. The amylin hormone is overexpressed in individuals with pre-diabetic insulin resistance or obesity leading to amylin oligomerization and deposition in pancreatic islets. Amylin oligomerization was implicated in the apoptosis of the insulin-producing β-cells. Recent studies showed that brain tissue from diabetic patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…Interestingly, similar to findings in Aβ plaques, ApoE was found to be co-deposited with IAPP amyloid [49][50][51]. However, the experimental data on the interaction between IAPP and ApoE are very scarce [52] in spite of the apparent importance of ApoE in IAPP-related pathologies [11,[49][50][51] and the crosslink between IAPP pathologies and AD as well as other types of dementia [44,47].…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…Interestingly, similar to findings in Aβ plaques, ApoE was found to be co-deposited with IAPP amyloid [49][50][51]. However, the experimental data on the interaction between IAPP and ApoE are very scarce [52] in spite of the apparent importance of ApoE in IAPP-related pathologies [11,[49][50][51] and the crosslink between IAPP pathologies and AD as well as other types of dementia [44,47].…”
Section: Introductionsupporting
confidence: 63%
“…In addition, an increasing number of experimental and clinical data indicate that IAPP aggregation can occur also in the brain, vascular system, heart, and kidneys [44][45][46]. IAPP deposition in the brain of type-2 diabetes patients with dementia and patients with AD [44,47] led to the hypothesis that IAPP along with Aβ is involved in AD pathology [44]. Animal studies showed also that overexpression of human IAPP in rats leads to neurological deficits and neuroinflammation [48].…”
Section: Introductionmentioning
confidence: 99%
“…The following two additional emerging hypotheses may be 'game changers' in regard to both the novel treatments of LOAD by repurposing insulin and insulin sensitizing medication and aiding in the understanding of the development and/or the continuum of progression in LOAD. Aα independent deposition in the perivascular regions and extracellular matrix, which may possibly interfere with Aβ efflux or clearance [169,170,171,172,173,174]. The amylin hypothesis involving the amyloidogenic Aα might also lead to the use of an amylin analog (pramlintide) for clinical study that has already been approved and utilized to treat type 1 and T2DM and known to improve glucose levels [175].…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…The following mechanisms are recognized for memory and cognitive deficits in DM: (1) hyperglycemia is considered the most important cause of diabetes complications as well as memory and cognitive impairments [11, 50]; (2) diabetes causes apoptosis and neuronal loss in the hippocampus and the frontal cortex, which are associated with cognitive impairment [14, 15, 51, 52]; (3) oxidative stress associated with cognitive dysfunction in diabetes increases neuronal damage and death through protein oxidation, DNA damage, and peroxidation of membrane lipids [13, 14, 51, 52]; (4) cholinergic (as one of the most important neurotransmitter systems involved in learning and memory formation mechanisms) dysfunction in the brain of diabetic rats via the increased activity of acetylcholinesterase (the enzyme responsible for degrading acetylcholine and terminating its physiological action) and decreasing levels of cholineacetyltransferase (the enzyme responsible for acetylcholine synthesis) contributes to DM memory impairment [16, 53]; (5) microvascular function change is another pathophysiological reason for cognitive impairment in diabetes, which is attenuated by some antioxidant agents [11]; and (6) changes in energy metabolism, cerebral blood flow, and the blood-brain barrier also cause memory and cognitive impairments [16, 54, 55]. As stated before, decreasing hyperglycemia in the diabetic groups with CoQ10 treatment may account for restoration of memory and cognitive function in DM.…”
Section: Discussionmentioning
confidence: 99%